Identifying scientific reasoning skills of science education students / Zulinda Ayu Zulkipli ... [et al.] - Zulkipli, Zulinda Ayu; Mohd Yusof, Mohamad Mubarrak; Ibrahim, Norezan; Dalim, Siti Fairuz (Universiti Teknologi MARA, 2020)
This article discusses a study carried out to investigate scientific reasoning skills among 82 science pre-service teachers at the Faculty of Education, Universiti Teknologi MARA (UiTM), one of the public universities in Malaysia. Undeniably, the development of general scientific abilities is critical to enable students of science, technology, engineering, and mathematics (STEM) to successfully handle openended real-world tasks in their future careers. Teaching goals in STEM education include fostering content knowledge and developing general scientific abilities. One such important ability is scientific reasoning. Scientific reasoning encompasses critical thinking skills as a vital learning outcome in modern science education. Lawson (1978) categorized scientific reasoning into four domains: Conservative Concept, Proportional Concept, Control Variable and Probabilistic Thinking, and Hypothetical-Deductive Reasoning. An instrument by Lawson (1978) was adapted for this study. The findings show that a majority of the science pre-service teachers possess low ability in scientific reasoning. It is also found that there was no significant difference among the science pre-service teachers of the physics, biology and chemistry disciplines when examined. The findings showed that Physics students had developed a higher ability in Conservative Concept, Proportional Concept, and Hypothetical-Deductive Reasoning and chemistry students had a higher ability in Control Variable and Probabilistic Thinking, whereas biology students had a moderate ability in the four scientific reasoning patterns.